2020
DOI: 10.1101/2020.02.10.941724
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The sperm epigenome does not display recurrent epimutations in patients with severely impaired spermatogenesis

Abstract: AbstractBackgroundIn the past 15 years, numerous studies have described aberrant DNA methylation of imprinted genes (e.g. MEST and H19) in sperm of infertile patients, but the prevalence and genomic extent of abnormal methylation patterns have remained unknown.ResultsUsing deep bisulfite sequencing (DBS), we screened swim-up spe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…To further investigate the absence of somatic cell DNA contamination in these TGC samples, we analysed the methylation levels at the 50 known maternally and paternally methylated imprinted control regions (ICR) [ 28 ]. As previously shown for uncontaminated sperm samples [ 16 ], the eight TGCs showed unmethylated oocyte DMRs and methylated sperm DMRs (Additional file 1 : Table S5, Additional file 2 : Fig. S2AB), consistent with the absence of somatic DNA contamination.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…To further investigate the absence of somatic cell DNA contamination in these TGC samples, we analysed the methylation levels at the 50 known maternally and paternally methylated imprinted control regions (ICR) [ 28 ]. As previously shown for uncontaminated sperm samples [ 16 ], the eight TGCs showed unmethylated oocyte DMRs and methylated sperm DMRs (Additional file 1 : Table S5, Additional file 2 : Fig. S2AB), consistent with the absence of somatic DNA contamination.…”
Section: Resultssupporting
confidence: 82%
“…A number of publications have reported that male infertility is associated with aberrant sperm DNA methylation profiles, particularly in imprinted genes [ 10 15 ]. However, we found no recurrent epimutations by deep bisulfite sequencing analysis of sperm from patients with severely impaired spermatogenesis ( n = 93) and controls ( n = 40), combined with whole genome bisulfite sequencing (WGBS) of selected samples [ 16 ]. This study, which is one of the largest in this field, rather revealed that the presence of residual somatic DNA in swim-up purified sperm samples and genetic variation are major confounders of methylation studies in sperm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected patient samples with qualitatively and quantitatively normal spermatogenesis (normal), and with cryptozoospermia (crypto). Clinical workup prior to surgery included full physical evaluation, hormonal analysis (including luteinizing hormone (LH), follicle stimulating hormone (FSH) and testosterone (T)) (38), semen analysis (39), and genetic analyses (including karyotype and screening for azoospermia factor (AZF) deletions). Exclusion criteria were known genetic causes of infertility, acute infections, testicular tumors, and a history of cryptorchidism.…”
Section: Patient Cohort Selectionmentioning
confidence: 99%
“…The patients for the WGBS were selected based on their responsiveness to the therapy, absence of co-morbidity, and non-smoking status (Supplementary Table 2, Additional File 1). For PTSD samples, WGBS libraries were prepared as previously described [29]. For the AN samples, 5 µg DNA at 50 ng/µl in water was used for library preparation and NGS sequencing on a HiSeq X platform (DKFZ Genomics & Proteomics Core Facility (GPCF) with 1 sample per lane.…”
Section: Whole-genome Bisulfite Sequencingmentioning
confidence: 99%